An organotypic model of oral mucosa cells for the biological assessment of 3D-printed resins for interim restorations - Alamo, Larissa; Cassiano, Fernanda Balestrero; Bordini, Ester Alves Ferreira; Stuani, Vitor Toledo; Pacheco, Leandro Edgar; Gallinari, Marjorie de Oliveira; Costa, Carlos Alberto Souza [UNESP]; Mondelli, Rafael Francisco Lia; Soares, Diana Gabriela (Elsevier, 2022)
Statement of problem: Three-dimensionally (3D) printed resins have become popular as a new class of materials for making interim restorations. However, little is known about how the fabrication parameters can influence biological compatibility with oral tissues. Purpose: The purpose of this in vitro study was to evaluate the effect of the postpolymerization time on the cytotoxicity of resins for printing interim restorations by using a 3D organotypic model of the oral mucosa. Material and methods: Cylindrical specimens were prepared with conventional acrylic resin (AR), computer-aided design and computer-aided manufacture (CAD-CAM) resin (CC), composite resin (CR), and 2 resins for 3D printing (3DP) marketed as being biocompatible. The 3DPs were submitted to postpolymerization in an ultraviolet (UV) light chamber for 1, 10, or 20 minutes (90 W, 405 nm). Standard specimens of the materials were incubated for 1, 3, and 7 days in close contact with an organotypic model of keratinocytes (NOK-Si) in coculture with gingival fibroblasts (HGF) in a 3D collagen matrix, or directly with 3D HGF cultures. Then, the viability (Live/Dead n=2) and metabolism (Alamar Blue n=6) of the cells were assessed. Spectral scanning of the culture medium was performed to detect released components (n=6) and assessed statistically with ANOVA and the Tukey post hoc test (α=.05). Results: Severe reduction of metabolism (>70%) and viability of keratinocytes occurred for 3DP resin postpolymerized for 1 minute in all periods of analysis in a time-dependent manner. The decrease in cell metabolism and viability was moderate for the 3D culture of HGFs in both experimental models, correlated with the intense presence of resin components in the culture medium. The resins postpolymerized for 10 and 20 minutes promoted a mild-moderate cytotoxic effect in the period of 1 day, similar to AR. However, recovery of cell viability occurred at the 7-day incubation period. The 3DP resins submitted to postpolymerization for 20 minutes showed a pattern similar to that of CR and CC at the end of the experiment. Conclusions: The cytotoxic potential of the tested 3DP resins on oral mucosa cells was influenced by postprinting processing, which seemed to have been related with the quantity of residual components leached.